Asymmetric synthesis of N-benzyl-5-methylhydroxy-piperidone and modular synthesis of C1-substituent tetrahydroisoquinolines (THIQ) and C2-symmetric bisisoquinolines (C2-BIQ) and their catalytic application in enantioselective Henry reaction - Khong, Duc Thinh (2015)
The core objective of this thesis is to develop effective strategies for the asymmetric synthesis of N-benzyl-5-methoxypiperidone, a common building block embedded in many biologically active compounds such as cytisine, vareniciline, paroxetine, tacamonine, and deplaincheine. Two main approaches were investigated: (1) chiral auxiliary, and (2) asymmetric catalysis. Both approaches successfully gave the enantiopure N-benzyl-5-methylhydroxy. With (S)-4-benzyloxazolidinone as the chiral auxiliary, asymmetric synthesis of (R)-N-benzyl-5-methylhydroxy-piperidone was achieved in six steps in 20% overall yield. The key step in this synthesis involved the diastereoselective aldol reaction of (S)-methyl 5-(4-benzyl-2-oxooxazolidin-3-yl)-5-oxopentanoate with 1,3,5-trioxane. The major diastereomeric aldol adduct was subjected to hydrolysis, amidation, chiral auxiliary removal and intramolecular cyclization to give the required enantiopure (R)-N-benzyl-5-methylhydroxy-piperidone.. Asymmetric catalysis through desymmetrization of 1,3-diols as precursor to N-benzyl-5-methoxy-piperidone, using chiral metal-ligand catalysts and lipases was investigated. Desymmetrization using Trost catalyst on our 1,3-diols only offered up 47% ee and 51% yield of monobenzoate product. On the hand, desymmetrization using lipase AK on our 1,3-diols provided up to 92% ee and 93% yield of (R)-monoacetate after optimization. In addition, we also found that desymmetrization of 1,3-diacetate gave the opposite enantiomer (S)-monoacetate in 95% ee and 41% yield. Therefore, in this approach, access to two enantiomers of N-benzyl-5-methoxy-piperidone was achieved in 70-80% yield in two steps after desymmetrization. The two asymmetric synthetic approaches provided a significant improvement in the overall yield of N-benzyl-5-methoxy-piperidone product. While the chiral auxiliary approach offererd enantiopure product in up to 20% yield afet six step, synthetic method using lipase provided up to 45% overall yield afeter six steps, which are higher comparing to Gallagher’s enzymatic resolution approach (approximately 15% yield after five steps). In addition, opposite enantiomeric product can also be conveniently obtained using the same type of lipase. Another objective of this work was to develop an effective modular synthesis of C1-substituent tetrahydroisoquinoline amino alcohols (THIQ) and C2-symmetric bisisoquinoline amino alcohols (C2-BIQ). The synthesis only comprised of two steps: H2SO4-catalyzed N-acyl Pictet Spengler reaction between (S)-4-benzyloxazolidinone and aldehyde substrates, followed by hydrolysis under alkali condition. The reactions proceeded smoothly under easy conditions and the products were obtained in high yields and purities. This synthetic approach provides modular, convergent methodology for the synthesis novel THIQ. To the best of our knowledge, this is the first diastereoselective approach towards the synthesis tetrahydroisoquinoline amino alcohol with tunable substituent group at C1. Application of these THIQs and C2-BIQs as chiral ligands in the Cu(II)-catalyzed asymmetric Henry reaction was also investigated. An optimal catalytic system of Cu(OAc)2.H2O-NNO THIQ (10 mol%) was found to promote the asymmetric Henry reaction between aromatic aldehydes and nitromethane to give the β-nitroalcohol products in up to 96% yield and up to 80% ee.